Colostrum and Colostrum Milk Production of PO and Pasundan Cows - Erdisa, Muhammad Iqbal Putra; Atabany, Afton; Putra, Bramada Winiar (Faculty of Animal Science, Universitas Brawijaya, 2026)
Beef cattle are important livestock in Indonesia. Besides meat, beef cows also produce colostrum, which is essential for calf immunity, growth, and survival during the early postpartum period. This study aimed to analyze colostrum and colostrum milk production of Ongole Crossbred (PO, abbreviation of “Peranakan Ongole”) and Pasundan cows. The research was conducted at the Mitra Mandiri Situbolang Cooperative, Indramayu, West Java, using 21 beef cows (PO and Pasundan). Colostrum was measured on the first day postpartum, while colostrum milk was defined as transition milk from colostrum to ordinary milk and was measured on days four and seven by weighing calves before and after suckling. Feed consumption and microclimate conditions were also recorded. Data were analyzed using an independent t-test. Results showed that there was no significant difference (? > 0.05) in the production of colostrum on the first day and the production of colostrum milk on the fourth day between the two breeds. However, there was a significant difference on day seven (? < 0.05), with PO cows producing more colostrum milk than Pasundan cows (4.29 kg vs 3.70 kg respectively). PO cows showed a greater production potential than Pasundan cows under the conditions of this study.